“Migrânea” or “enxaqueca”: A historical and semantic review - Soares, Adriana de Almeida; Fortes, Yasmine Maria Leódido; Souza, Wallyson Pablo de Oliveira; Silva-Néto, Raimundo Pereira (Headache Medicine, 2023)
Introduction Headache is as old as the emergence of man on earth. A classification for headaches has been suggested for many centuries. After the invention of writing, numerous words were created to designate different types of headache. Objective The objective of this review was to discuss the historical and etymological aspects of the terms “migrânea” and “enxaqueca”. Methods This study was an integrative review using articles with historical data on the etymology of the terms “migrânea” and “enxaqueca” and their evolution over the years. Results The terms “migrânea” and “enxaqueca” have Greek and Arabic origins, respectively. Both describe a neurological syndrome characterized by headache and other associated symptoms. Usually, sufferers of this disease are more familiar with the term “enxaqueca” and confuse it with headache, while health professionals prefer the term “migrânea”. Conclusions After so many years that the term "migrânea" has been used, it would be a step backwards to use the term "enxaqueca" again, especially because "migrânea" has been adopted by young neurologists, including those from other specialties.